The measurement of the diffusion coefficients of ferrocene and ferrocenium and their temperature dependence in acetonitrile using double potential step microdisk electrode chronoamperometry - Wang, Y; Rogers, E; Compton, R (2010)
The diffusion coefficients of both ferrocene (Fc) and ferrocenium (Fc +) in acetonitrile containing 0.1 M tetra-n-butylammoniumperchlorate (TBAP) or 0.1 M tetra-n-butylammoniumhexafluorophosphate (TBAPF6) are reported, determined using the technique of double potential step chronoamperometry at a microdisk electrode. Activation energies of diffusion, Ea,D are calculated for both redox species in each system. Diffusion coefficient ratios of the diffusion coefficients of Fc compared to that of Fc+ in each case were found to be very close to 1. Activation energies of diffusion, Ea,D, for ferrocene and ferrocenium in the acetonitrile/perchlorate system were determined as 6.5 (±0.2) and 7.2 (±0.5) kJ mol-1, respectively. Similar values were determined for the acetonitrile/hexafluorophosphate system: 7.1 (±0.1) kJ mol -1 for Fc and 7.4 (±0.3) kJ mol-1 for Fc +. Cyclic voltammograms were recorded for ferrocene oxidation in both acetonitrile/electrolyte systems and it was observed that the E1/2 values were similar and independent of the electrolyte used. © 2010 Elsevier B.V. All rights reserved.